1-(4-{[(E)-4-Methylbenzylidene]amino}phenyl)ethanone oxime - Zhao, L.; Ng, S.W. (International Union of Crystallography, 2010)
In the title compound, C(16)H(16)N(2)O, the dihedral angle formed by the two benzene rings is 50.3 (1)degrees. In the crystal structure, molecules are linked into an infinite one-dimensional supramolecular structure by intermolecular O-H center dot center dot center dot N hydrogen-bond interactions.